Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and hand grip strength in U.S. adults - Huimin Wang; Qihui Huang; Xiaojia Feng; Xiaowei Zheng (Scientific Reports)
Abstract Non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is an indicator of imbalance in lipid metabolism and has been associated with a variety of metabolic diseases. Hand Grip Strength (HGS) is an important indicator for assessing muscle function and overall health. The aim of this study was to investigate the relationship between NHHR and HGS, with the aim of revealing how lipid metabolism affects muscle strength and may provide an early indication of metabolic health and muscle dysfunction. We collected demographic and clinical data from 6,573 adults aged 20–60 years from the National Health and Nutrition Examination Survey (NHANES) database from 2011 to 2014.NHHR is defined as the ratio of total cholesterol minus high-density lipoprotein levels (HDL-C) divided by HDL-C. HGS is expressed as relative grip strength and is defined as the sum of the maximum readings for each hand/body mass index ratio. Among the data analysis techniques used in this study were multifactor linear regression, smoothed curve fitting, subgroups, and interactions. There was a negative correlation between NHHR and HGS in the 6573 participants included. After adjusting for all covariates, each unit increase in log2-NHHR was associated with a 0.28 [−0.28 (−0.31, −0.26)] decrease in HGS, and this negative correlation remained stable across subgroups (p < 0.01 for the test of trend). The analyses also identified a nonlinear association between NHHR and HGS with an inflection point of 1.74. Interaction tests showed that the negative correlation between NHHR and HGS differed significantly across age, gender, and stratification by diabetes status. Our study suggests that there may be a negative correlation between HGS and NHHR in adults aged 20–60 years in the U.S. Considering that a decline in HGS is an important manifestation of sarcopenia, it may be relevant to the prevention and control of sarcopenia through close detection and management of NHHR.